If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 7 = 6 Reorder the terms: 7 + y = 6 Solving 7 + y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + y = 6 + -7 Combine like terms: 7 + -7 = 0 0 + y = 6 + -7 y = 6 + -7 Combine like terms: 6 + -7 = -1 y = -1 Simplifying y = -1
| 2x+9y=42 | | 8x^3-64=0 | | x=12-3y | | X=296+9x | | 4(3+x)+10=11(x-6)1 | | X-296=9x | | 24y=768 | | -3x^2+2x+440=0 | | -3x^2-2x+440=0 | | 4x+11=4x-24 | | 3x+y=21 | | 2n+5n+7=-41 | | 9x=8x-4 | | x^2+1=x^2-3 | | 16-2x=4(7+x) | | 6y+15= | | 16-2x=49(7+x) | | 2x^3+12x^2-4x-24=0 | | 1.6a-0.6a-2.2=9.3-2.3 | | -3(x+9)-44=7-54 | | 22x+7-25x=6-8 | | (x+2)(x-4)=7 | | (x-4)+(x+5)=0 | | -1-(-3)= | | 6x+14-5x=-3-10 | | 12x=4(8x+25) | | 1.3y-0.3y-5.4=-3.7-5.9 | | 91y=10(9y+25) | | 7-7=3x+2x | | 66=6t-17t | | 9x-14=94 | | x(x(x(x+7)+16)+14)+4=0 |